2005
DOI: 10.1111/j.1464-410x.2005.05307.x
|View full text |Cite
|
Sign up to set email alerts
|

Stone‐bearing live‐donor kidneys for transplantation

Abstract: OBJECTIVE To evaluate potential donor kidneys with asymptomatic calculi detected during screening, and the management of the calculus before, during and after transplantation, as with fewer live donors, marginal kidneys and donors are a significant subgroup in renal transplantation. PATIENTS AND METHODS Five live‐related donors, with one incidentally detected calculus during their routine evaluation, were accepted for transplantation. Of these, three were detected only on spiral computed angiography. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
1
22
0
5
Order By: Relevance
“…There are few case series which have shown that the short-and medium-term results are excellent both in donor and recipient follow-up after bench ureteroscopy [12][13][14][15][16][17][18]. We need long-term results with large number of patients to establish bench URS/RIRS as treatment of choice for this specific category of patients.…”
Section: Resultsmentioning
confidence: 88%
“…There are few case series which have shown that the short-and medium-term results are excellent both in donor and recipient follow-up after bench ureteroscopy [12][13][14][15][16][17][18]. We need long-term results with large number of patients to establish bench URS/RIRS as treatment of choice for this specific category of patients.…”
Section: Resultsmentioning
confidence: 88%
“…19 A smaller right kidney and undiagnosed lesions within the right donor kidney were also indications for right donor nephrectomy. 20 In our series, if the relative function is lower, and if there is a renal cyst or tiny stone (<5 mm) in the right kidney, the right kidney was removed to benefit the donor. A retrospective study of 25 living donor kidneys with cysts found no cystrelated complications in transplanted organs, 21 similar to the results in our series.…”
Section: Commentmentioning
confidence: 99%
“…Stone-free rates have ranged from *60% to 100% for stones < 4 mm in small series with < 2 years mean follow-up. 4,5 Conversely, Klingler and colleagues 6 noted the development of ureteral obstruction after transplantation of stone-containing kidneys in 4/5 patients necessitating nephrostomy tube placement, including all patients with calculi > 4 mm. 6 Endoscopic extraction immediately after donor nephrectomy is another option that has been previously described with minimal risk of recurrence.…”
Section: Introductionmentioning
confidence: 94%